Optimizing Children's Health: The Importance of Immunization at Posyandu - Herlianty, Herlianty; Sridahrianti, Evi; Rasdin, Rasdin (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Immunization is the most effective and efficient public health effort in preventing diseases and reducing mortality rates such as smallpox, polio, tuberculosis, hepatitis B, measles, rubella and congenital rubella syndrome (CRS), tetanus, pneumonia (pneumonia) and meningitis (inflammation of the lining of the brain). The purpose of immunizing infants who have never been immunized and infants whose immunizations are incomplete. As an alternative solution to the problems that have been identified, immunization counseling activities are carried out for infants who have never been immunized or infants who are incompletely immunized. The methods used in this activity use several types of methods, namely: Counseling about side effects after immunization, and distribution of leaflets There were as many as 5 children identified in immunization activities, and there was an increase in knowledge for mothers and posyandu cadres after Community Service activities had gained knowledge about immunization and after being evaluated through a question and answer session, many did not know what the benefits and effects were side after immunization. It is expected that mothers who have babies/toddlers routinely bring their children to the nearest Puskesmas or Posyandu to get complete immunizations.